The Level of Administrative Work From The Standpoint Of The Secondary School Principals Pressure And Its Relationship With Some Variables"A Field Study In Latakia Province" - Mansour , Smaia; Wazzan, Rawan (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research aims to identify the level of administrative work pressures faced by secondary school principals in Latakia province, according to the sources: the relationship with the educational administration, the relationship with the faculty members, the relationship with the students and the local community, the nature of administrative work, lack of job satisfaction, and to study the differences between managers in the level of administrative work stress (sub-areas and the scale as a whole) depending on the variables: sex, years of experience in administrative work, educational qualification, marital status, the school time. Find adopted descriptive analytical method, it has been developed and distributed a questionnaire on the sample of 152 principals, and returned them (141) questionnaire complete and valid for statistical analysis, and response rate (92.76%). And using appropriate statistical methods was the most important results: The administrative work pressure in the secondary school principals in Latakia province level is the high level for all sources and scale as a whole with the exception of the pressure caused by the relationship with the educational administration was moderate, as these pressures variables sex level is affected, and years of experience in administrative work, academic qualification, marital status, and the period of school time. The results showed that female managers feel the level of pressure is higher than managers administrative work; as well as the greater experience in administrative work among secondary school principals level, the less administrative work pressure level; also secondary school principals suffering from advanced degrees from the high pressure management work compared with the qualified level (Average Institute, a university) leave; the other hand, the marital status categories (Widowed, Divorced, Married) feel a high level of pressure in the administrative work compared with the singles category; and these differences have emerged for all the sources and scale as a whole with the exception resulting from the relationship pressure with educational administration. As for the durability Managers at the same time schools are on double the level of high pressure management work compared with managers who work in single-shift schools, and so for all the sources and scale as a whole.